2014
DOI: 10.3389/fpsyg.2014.00356
|View full text |Cite
|
Sign up to set email alerts
|

Failure to see money on a tree: inattentional blindness for objects that guided behavior

Abstract: How is it possible to drive home and have no awareness of the trip? We documented a new form of inattentional blindness in which people fail to become aware of obstacles that had guided their behavior. In our first study, we found that people talking on cell phones while walking waited longer to avoid an obstacle and were less likely to be aware that they had avoided an obstacle than other individual walkers. In our second study, cell phone talkers and texters were less likely to show awareness of money on a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 56 publications
1
41
1
Order By: Relevance
“…Therefore, it is possible that younger adults similarly disengaged from visually scanning their environment under conditions of Cognitive Load due to the reduced availability of cognitive resources necessary to store this ‘spatial map’ of their surroundings in working memory. This latter suggestion is supported by research demonstrating how walking while simultaneously talking on a cell phone can cause ‘situational blindness’, whereby younger adults fail to perceive unusual objects along their walking path, such as a unicycling clown [34] or a tree with money attached to the leaves [35]. However, as gaze behavior was not measured in this previous research, it is difficult to assess whether this ‘situational blindness’ was in fact a consequence of individuals failing to visually scan their environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is possible that younger adults similarly disengaged from visually scanning their environment under conditions of Cognitive Load due to the reduced availability of cognitive resources necessary to store this ‘spatial map’ of their surroundings in working memory. This latter suggestion is supported by research demonstrating how walking while simultaneously talking on a cell phone can cause ‘situational blindness’, whereby younger adults fail to perceive unusual objects along their walking path, such as a unicycling clown [34] or a tree with money attached to the leaves [35]. However, as gaze behavior was not measured in this previous research, it is difficult to assess whether this ‘situational blindness’ was in fact a consequence of individuals failing to visually scan their environment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to disrupting the automaticity of motor performance, researchers have indicated that reinvestment can influence the allocation of attention during gait. Much in the same way as performing a cognitive dual-task while walking can reduce an individual's ability to perceive environmental cues [34,35], researchers have demonstrated that conscious monitoring and control of movement may similarly impair the perception of external information during locomotion [36,37]. Masters and colleagues [33] argued that cognitive resources are required to consciously attend to the process of moving.…”
Section: Introductionmentioning
confidence: 99%
“…As the authors show in an ingenious experiment, people talking or texting on cell phones avoided a low-hanging branch impeding their route yet failed to register the bizarre fact that three-dollar bills had been clipped to the branch (Hyman et al, 2014, Figure 1). The authors also point out that avoiding obstacles while distracted is typically not all-or-none: “For example, a driver needs to respond differently to a large truck, a car, a bicyclist, and a pedestrian” (Hyman et al, 2014, p. 6).…”
Section: Attention and Distractionmentioning
confidence: 99%
“…Other work by Dr. Hyman has included hanging actual dollar bills on a tree in a pathway. In this case, distracted passerby actually moved their heads to not get smacked in the face, but they still didn't notice the money in the trees (Hyman, Sarb, & Wise-Swanson, 2014).…”
Section: Wait Money Does Grow On Trees?mentioning
confidence: 98%